Log in to add a comment

## Answers

wherein it is in terms in x and y

like

(x+y)(x-y) = x²-y²

it is a special product in which you can use it in a situation like this

(x+3)(x-3)=0

using the special product that we know

(x+3)(x-3)= x² - (3)²

it will take the hassle it expanding it to

(x+3)(x-3) = x² + 3x - 3x - 3(3)

=x² + 3²

you can search in google for Special products and Factoring for more Special Products and Factoring.

sorry but we are not allowed to post url in the answers

and they are too long to type.. hope this helps you.

comment for further questions.